Mercapto-functionalized scaffold improves perovskite buried interfaces for tandem photovoltaics - Jianan Wang; Shuaifeng Hu; He Zhu; Sanwan Liu; Zhongyong Zhang; Rui Chen; Junke Wang; Chenyang Shi; Jiaqi Zhang; Wentao Liu; Xia Lei; Bin Liu; et al. (Nature Communications)
Abstract Tandem photovoltaics hold great potential to surpass the efficiency limit of single-junction solar cells. Detrimental structural defects and chemical reactions at buried interfaces of subcells considerably impede the performance of integrated tandems. Here, we devise a mercapto-functionalized mesoporous silica layer as a superstructure at the buried interface to modulate the crystallisation, eliminate nanovoids, passivate defects, and suppress the oxidation of Sn(II) in the tin–lead perovskite films, contributing substantially to reduce charge carrier losses and improve stability in positive-intrinsic-negative structured devices. Consequently, the tin–lead perovskite single-junction cells show efficiency values of up to 23.7% with the best open-circuit voltage of 0.89 V. With the enhanced subcells, our double-junction tandems show efficiency values of 29.6% (certified 29.5% and steady-state 28.7%) and 24.7% on solar cells and 11.3 cm2 mini-modules, respectively. Encapsulated tandems maintain 90% of initial efficiency after 445 h of maximum power point tracking under simulated 1-sun illumination.